Wireless electronic notice board using IoT - Amutha M; Hemalatha S; Kavitha K R; Jayashree P (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
A notice board is now considered to be a crucial element for universities, companies, or public places like hospitals, bus stations, and transport hubs. Nevertheless, using paper notes mounted on a noticeboard is a time-consuming and expensive technique that wastes a lot of material, manpower, and time. The message or information is used to effectively show the public data, although it could be hard to modify the notifications quickly. We have created and set up an advanced "Wireless Notice Board" in this paper. The system can be enhanced by employing an Android app on Wi-Fi connected smartphones and tablets to deliver the most current information to a reasonably priced programmed microcontroller.